Earthworms of Belarus (Annelida: Megadrili) - Shekhovtsov, Sergei V.; Derzhinsky, Yevgeniy A.; Ermolov, Sergei A.; Kim-Kashmenskaya, Maria N.; Poluboyarova, Tatiana V.; Kotsur, Vladimir M.; Golovanova, Elena V. (Zootaxa, 2023)
A survey of the earthworm fauna of Belarus that included most of its territory was performed in this study. One genus, three species and one subspecies were reported for the first time. The fauna of Belarus thus comprises 17 species and two subspecies. Detailed maps for all of the reported species were constructed.